Who deserves to access their rights? Inequality in the action against non-take-up - Max Lovey; Jean-Michel Bonvin (Culture, Practice & Europeanization)
The issue of non-take-up has increasingly been brought to light by scholars and field actors during the past decade. As a result, the issue gained political traction, and programs have been designed to reduce it. In canton Geneva, Switzerland, a town’s social services have recently launched two programs to enhance access to social rights. In this paper, we explore, notably through the lens of the deservingness literature, the variety of ways in which sub-groups of the population interact with the local authorities’ commitment to tackle non-take-up. Based on 45 semi-structured interviews with recipients, social workers and managers of these municipal programs, as well as stakeholders at cantonal level, we assess how the design, implementation and reception of the programs by their targeted population influence their unequal outcome. Our results show how the perception of various sub-groups of the population as more or less deserving informs how social policy is designed at macro level; implemented by state administration at federal and cantonal level and mediated by action against non-take-up at municipal level; and received by beneficiaries at micro level. By reproducing the deservingness rationale identified in the literature, local action against non-take-up tends to fuel a cumulative (dis-)advantage dynamic, and therefore reinforce or reproduce dynamics of inequality between sub-groups of the population whose starting point in terms of access to social rights does not seem to differ significantly.